2012
DOI: 10.1128/jcm.06180-11
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila Sequence Type 1/Paris Pulsotype Subtyping by Spoligotyping

Abstract: L egionella spp. are ubiquitous bacteria present in natural and artificial water systems. Inhalation of Legionella spp. in aerosolized water droplets from contaminated water sources is known to cause a type of pneumonia called Legionnaires' disease (LD). In the event of an LD outbreak, the successful outcome of an epidemiological investigation can help prevent further cases by rapidly identifying and containing the source of contamination.Legionella pneumophila is responsible for more than 90% of the cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…For other bacteria, the spacer DNAs of the CRISPR/Cas systems are used for epidemiological subtyping of isolates (spoligotyping) (Ginevra et al, 2012;Price et al, 2007;Sorek et al, 2008). It would be interesting to analyse, if the CRISPR/Cas system is usable to generate a CRISPR/Cas spacer based spoligotyping for Francisella.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For other bacteria, the spacer DNAs of the CRISPR/Cas systems are used for epidemiological subtyping of isolates (spoligotyping) (Ginevra et al, 2012;Price et al, 2007;Sorek et al, 2008). It would be interesting to analyse, if the CRISPR/Cas system is usable to generate a CRISPR/Cas spacer based spoligotyping for Francisella.…”
Section: Resultsmentioning
confidence: 99%
“…In S. thermophilus this system was shown to confer resistance of the bacteria to specific phages (Barrangou et al, 2007). The spacer DNA in general is very specific for each strain and therefore used for epidemiological subtyping (spoligotyping) (Ginevra et al, 2012;Price et al, 2007;Sorek et al, 2008). Since Ft. novicida and F. philomiragia are species known to be associated with aquatic habitats and therefore may get 8 into contact with various phages and plasmids, we had a closer look to the spacer DNA of the identified CRISPR systems.…”
Section: Analysis Of the Spacer Dnas Of The Crispr-1 And Crispr-2 Sysmentioning
confidence: 99%
“…The protocol used for the spoligotyping on a membrane has been published previously (9). For the microbead-based spoligotyping, the DR-F primer was labeled at the 5= end with biotin (instead of digoxigenin [DIG] as for the membranebased method).…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we showed that in certain cases, some strains that are indistinguishable (either by SBT or by PFGE), particularly within the L. pneumophila ST1/Paris pulsotype, could be efficiently classified further using the genetic diversity of their clustered regularly interspaced short palindromic repeats (CRISPRs), and we developed a membrane-based method, spoligotyping (9). The name of this technique is based on that of the original spoligotyping method, which was first used for Mycobacterium tuberculosis complex (MTC) (10).…”
mentioning
confidence: 99%
“…Spoligotyping is based on differences between CRISPR-Cas systems to identify bacterial strains (315). This technique helps investigations of evolution and geographical and/or historical studies (316,317) and permits the identification of microbial populations (318) or the analysis of pathogen outbreaks (319). New spacer repeat units are inserted in 5= extremities of CRISPR arrays, which provide information on recent infections.…”
Section: Genetic Elements Controlling the Stability Of Mobile Elementsmentioning
confidence: 99%